Adolescent Technology, Sleep, and Physical Activity Time in Two U.S. Cohorts. Issue 4 (May 2021) - Fomby, Paula; Goode, Joshua A.; Truong-Vu, Kim-Phuong; Mollborn, Stefanie
The advent of Internet-enabled mobile digital devices has transformed U.S. adolescent technology use over the last decade, yet little is known about how these changes map onto other health-related behaviors. We provide a national profile of how contemporary technology use fits into adolescents' daily health lifestyles compared with the previous generation, with particular attention to whether and for whom technology use displaces time spent in sleep or physical activity. Time diaries were collected from 11- to 17-year-olds in 2002-2003 ( N = 1, 139) and 2014-2016 ( N = 527) through the U.S. Panel Study of Income Dynamics Child Development Supplement. Contemporary adolescents spent 40 minutes more per week in technology-focused activities, but their composition was more varied compared with the earlier cohort. Contemporary technology use was predictive of less time in physical activity, and adolescents who engaged in frequent video game play spent less time in physical activity compared with peers with other technology use profiles.